Early education and clinical exposure on hand hygiene: a key for better compliance - Thakuria, Bhaskar; Pandey, Anita; Chaturvedi, Priyanka (International Journal of Research in Medical Sciences, 2019)
Background: India is underperforming when it comes to compliance to hand hygiene. Early education on followed by regular hand hygiene audits can bring positive changes in infection control practices. Methods: Group I included the 3rd Semester MBBS students who had early education and training on hand hygiene and Group II included the post graduate residents who were exposed to Hand Hygiene later in their carrier were followed up for compliance of WHO Hand Hygiene moments for four months. Compliance among students and residents were observed and compared. Results: Compliance rate was more (40.4%) among medical students as compared to residents (17%). The After moments had a better compliance than Before moments among both students and residents. The difference in the compliance rate was statistically significant. Conclusions: Early clinical exposure of the students to any problem, is the key for better compliance thus explaining the better compliance rate among medical students. Better HH practice can bring down prevalence of Healthcare associated infection by multidrug resistant organism which is a major concern today.